PET-CT changes the management and improves outcome in patients with recurrent colorectal cancer - Tural, Deniz; Selçukbiricik, Fatih; Sağer, Sait; Akar, Emre; Yıldız, Özcan; Serdengeçti, Süheyla (Medknow Publications, 2014)
Background: The present study aims to analyze the impact of positron emission tomography/computed tomography (PET/CT) on management change in patients with suspected or proven colorectal cancer recurrence, and to assess the effect of this management change on progression-free survival (PFS) and overall survival (OS). Materials and Methods: We retrospectively evaluated 122 patients with suspected potentially resectable recurrent colorectal cancer who underwent PET/CT scan. We determined management plans for these patients before and after the PET/CT examination. Results: While previous conventional imaging studies had revealed solitary metastases, additional sites of disease were determined by PET/CT scan in 52/122 (42%) patients. PET/CT examination results changed the treatment plan to curative intent in 35 (37%) patients. While the median PFS was 22 months (95% CI, 11.2-32.6 months) among the patients planned to receive curative treatment after the PET/CT scan, it was 11 months (95% CI, 8.1-13.9 months) in patients planned to receive curative treatment before the PET/CT examination, and the difference between median PFS durations was statistically significant (HR, 0.51 [95% CI, 0.32 - 0.88], P = 0.004). Furthermore, OS was significantly longer in patients planned to receive curative treatment after the PET/CT scan (27 months [95% CI, 22.1-31.9]) compared with those who received curative treatment before the PET/CT scan (21 months [95% CI, 15.6 - 26.4]), and the difference was statistically significant (HR, 0.63 [95% CI, 0.42 - 0.89], P = 0.045). Conclusion: The present study demonstrates the significant impact of PET/CT on the management and outcome in patients with recurrent colorectal cancer.
Keywords: Improved Outcome; Management Change; Recurrent Colorectal Cancer; Positron Emission Tomography/Computed Tomography Scan